PENGARUH ADOPSI INOVASI TEKNOLOGI E-BANKING TERHADAP KINERJA DENGAN EFEKTIVITAS PENGENDALIAN INTERN SEBAGAI VARIABEL MODERASI (THE EFFECTS OF THE ADOPTION OF E-BANKING TECHNOLOGY INNOVATION ON THE PERFORMANCE WITH THE INTERNAL CONTROL EFFECTIVENESS AS THE MODERATING VARIABLE: AN EVIDENCE FROM COMMERCIAL BANKS IN INDONESIA) - Sutarti, Sutarti; Syakhroza, Akhmad; Diyanty, Vera; Dewo, Setio Anggoro (Jurnal Akuntansi dan Keuangan Indonesia, 2019)
This study aims to test empirically the effects of e-banking innovation technology’s adoption on the performance of commercial banks in Indonesia with the effectiveness of internal control as the moderating variable. The population in this study are commercial banks in Indonesia during the period 2010-2016 excluding Islamic commercial banks. The samples in this study consisted of 47 banks with 229 observations. The samples were chosen based on the purposive sampling technique. This study estimated the parameters of a panel data set using GLS-RE method. The study found that the number of adoption types of e-banking technology innovations negatively affects the bank performance. The effectiveness of internal control could reduce the negative influence of the e-banking technology innovation adoption on banks’ performances. The results of this study have several implications for the regulator and the bank entities, especially in developing countries such as Indonesia regarding the importance of bank internal controls in mitigating risks, such as operational risks, reputation risks and legal risks that may arise with the adoption of e-banking technology innovations in banks, as stipulated by Circular Financial Services Authority No. 38/POJK.03/ 2016 and Basel (2001), and Circular Financial Services Authority No. 21/SEOJK.03/2017 related to the application of risk management in the application of information technology in banks.